(3GdQSGdI GdJi CQSdJ Edi hdi GdYgO (B( (3YgO GdeSdejf YHO GdQMjef Hf EdjGS(B)s - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf Ld PcQg hHg CSJYjf ai LejY GdCehQ CeG HYO abO MGf hdi GdYgO Cf jcTa GdbfGY hjYQa de JSei GHf Ye CejQ GdeDefjf s
(3BNQgG (B:s
(3hjbQ dg HGdYHhOjI EP dGMSH hdG fSH hef bGdg NSQ GdOfjG hGdBNQI Pdc gh GdNSQGf GdeHjf JeJ GdQSGdI hGdMeO dehdGfG hMOg hgh MSHi hfYe GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B27s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds